External hemostasis / internal repair double-layer composite stent and its preparation and application

By adopting a double-layer composite scaffold design in wound repair materials, combining radio-oriented nanofiber membranes and gradient pore structure chitosan sponge, the existing materials have both effective effects in hemostasis and tissue repair, and the effect of rapid hemostasis and promoting wound repair is achieved.

CN116019981BActive Publication Date: 2025-03-21AOMEI MEDICAL SUPPLIES CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211114014.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-14
Publication Date
2025-03-21
Estimated Expiration
2042-09-14

AI Technical Summary

Technical Problem

The existing materials lack both hemostasis and tissue repair, and the preparation method of composite structural scaffolding has the problem of hardening the bonding layer or destroying the original properties.

Method used

The design of a double-layer composite scaffold, including an inner radiation-oriented array nanofiber membrane and an outer gradient pore structure chitosan sponge, enhances interlayer binding force through the introduction of dopamine, and realizes the construction of gradient pore structure by controlling the pore size.

Benefits of technology

It achieves rapid hemostasis and promotes wound repair, avoids the problem of hardening of the bond layer, has good biocompatibility and non-toxicity, and the wound closure rate can reach 97%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116019981B_ABST
    Figure CN116019981B_ABST
Patent Text Reader

Abstract

The present invention relates to an external hemostasis / internal repair double-layer composite stent and its preparation and application, comprising an inner layer of radially oriented nanofiber membrane and an outer layer of chitosan sponge with a gradient pore structure. The outer layer of the sponge with a gradient pore structure in the present invention can quickly absorb blood from the wound and stop bleeding under the action of the differential capillary effect; the radially oriented fiber layer has a cell guiding effect, and the radially oriented fiber structure can realize the release of chemokines at different concentrations from the center to the edge of the wound surface, which can guide the migration of stem cells around the damaged part to the center of the wound, while promoting the growth and adhesion of fibroblasts and accelerating wound repair.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of functional stents, and in particular relates to an external hemostasis / internal repair double-layer composite stent and its preparation and application. Background Art

[0002] Hemostasis and tissue repair are two important links in the wound repair process. The materials currently prepared only have hemostasis or tissue repair effects, and rarely have both hemostasis and wound healing effects. For example, sponge materials have high porosity, so they have high blood absorption capacity and can achieve hemostasis, but their hemostasis and wound repair abilities need to be improved. Nanofiber materials can promote cell adhesion and proliferation by simulating extracellular matrix structures, and have broad application prospects in promoting tissue repair, especially orderly oriented fibers can significantly promote cell migration and accelerate wound closure, but they do not have hemostasis. In recent years, composite dressings have attracted widespread attention. However, how to combine materials of different structures or properties into one is still a challenge. In the prior art, the preparation of composite structure scaffolds mostly adopts the method of adding a binder to form a bonding layer, but the bonding layer is usually harder, or destroys the original properties of the two materials, or causes its application to be limited, and there are potential hazards, affecting wound healing. Chitosan has many advantages such as good biodegradability, biocompatibility, non-toxicity, antibacterial, immune enhancement, and wide sources. Therefore, it is widely used in artificial skin, hemostatic materials, etc., and shows great potential in the field of biomedical materials. Summary of the invention

[0003] In view of the defects of the prior art, the technical problem to be solved by the present invention is to provide an external hemostasis / internal repair double-layer composite stent and its preparation and application.

[0004] The invention discloses a double-layer composite stent, which comprises an inner layer of radially oriented array nanofiber membrane and an outer layer of chitosan sponge with a gradient pore structure.

[0005] The double-layer composite stent comprises: an inner layer radially oriented nanofiber membrane 1, an outer hemostatic chitosan sponge macroporous region 2, and an outer hemostatic chitosan sponge microporous region 3; wherein the pore size range of the outer hemostatic chitosan sponge macroporous region is 120-200 μm; and the outer hemostatic chitosan sponge microporous region is 30-80 μm.

[0006] The radially oriented nanofiber membrane is specifically:

[0007] The radially oriented nanofiber membrane is composed of 9 fiber colonies, and the average thickness at the center of the 9 fiber colonies is 30 to 65 μm; in each fiber colony, the length direction of the fiber is radially distributed around the center of the fiber colony, and the density of the fiber is gradually reduced along the radial direction;

[0008] The distribution of the 9 fiber colonies is as follows: the center of the fiber colony is regarded as the fiber colony, with one of the fiber colonies as the center, and the other 8 fiber colonies form a ring-shaped array fiber colony group, the ring-shaped array fiber colony group is distributed in a circle, and each fiber colony on the ring-shaped array fiber colony group is distributed at equal angles along the circumference.

[0009] The fiber density at the connection point between any two fiber colony centers is higher than that at other locations between the two fiber colonies, and the connection point refers to a line connecting the centers of the two fiber colonies.

[0010] A method for preparing a double-layer composite stent of the present invention comprises:

[0011] (1) preparing two chitosan solutions with different dopamine contents: dissolving chitosan in a solvent, stirring for 12 h until uniform, adding different amounts of dopamine, stirring in a water bath, and then adding genipin, stirring for 10 min, to obtain mixed solution A and mixed solution B;

[0012] (2) Place the radially oriented nanofiber membrane at the bottom of the template, then first pour the mixed solution A of step (1) onto the surface of the fiber membrane, then pour the mixed solution B onto the mixed solution A, place it at 4°C for 12-16 hours to fully cross-link the chitosan with genipin, then place it in liquid nitrogen for pre-freezing for 10-20 minutes, take it out and place it in a freeze dryer for freeze-drying for 12-24 hours, then soak it in ethanol to chemically combine the chitosan sponge with the fiber membrane with dopamine to increase the interlayer force, soak it in PBS solution to wash off the excess ethanol, then take it out and place it in liquid nitrogen for pre-freezing for 10-20 minutes again, then place it in a freeze dryer for freeze-drying for 3-6 hours to obtain a double-layer composite scaffold.

[0013] The preferred method of the above preparation method is as follows:

[0014] The viscosity of chitosan in step (1) is: <200 mPa s.

[0015] In the step (1), the concentration of dopamine in the mixed solution A is 2-5 mg / mL; the concentration of dopamine in the mixed solution B is 7-10 g / mL.

[0016] In the step (1), the concentration of chitosan after being dissolved in the solvent is 10-20 mg / mL; the solvent is acetic acid with a volume percentage concentration of 1%; the mass ratio of chitosan to dopamine is (1-4):1; the mass ratio of chitosan to genipin is (20-25):1.

[0017] The water bath stirring in step (1) is stirring at 40° C. for 1 h until the solution is uniform.

[0018] In the step (2), the template is a circular hole plate; the diameter of the circular hole plate is 1.5 cm; the perfusion volume of the mixed solution A and the mixed solution B is 0.5-0.8 mL.

[0019] The ethanol soaking in step (2) is soaking in 70-90% ethanol by mass concentration for 6-10 hours; soaking in PBS solution for 3-4 times, each time for 3-5 minutes.

[0020] The radially oriented nanofiber membrane in step (2) is a polymer radially oriented array nanofiber membrane; the polymer is one or more of polycaprolactone (PCL), polylactic acid-glycolic acid copolymer (PLGA), collagen, and gelatin.

[0021] The radially oriented array nanofiber membrane in step (2) is prepared by the following method:

[0022] The polymer is dissolved in a solvent and stirred for 24-96 hours until it is completely dissolved to obtain a spinning solution, which is then placed in a micro-syringe and subjected to electrospinning and vacuum drying to obtain a radially oriented array nanofiber membrane; wherein the receiving device used for electrospinning includes a printed circuit board and a ring electrode.

[0023] The printed circuit board includes an insulating substrate, 9 pads, two connectors, 9 wires and 9 needle-tip electrodes; the 9 pads are distributed on the insulating substrate in the following manner: the pad is regarded as a point, one pad is distributed in the exact center of the insulating substrate, and the remaining 8 pads constitute a circular array pad group, and the pads on the circular array pad group are distributed at equal angles along the circumference; the center of the ring is the exact center of the insulating substrate.

[0024] The bottom of the annular electrode is fixed on the insulating substrate, and from the top perspective of the annular electrode, the circle formed by the inner wall of the annular electrode and the circle formed by the annular array pad group form concentric circles, and the radius of the circle formed by the annular array pad group is half of the circle formed by the inner wall of the annular electrode; the radius of the circle formed by the inner wall of the annular electrode is 5-10mm; and the thickness of the annular electrode (made of stainless steel) is 1mm and the height is 27mm;

[0025] The needle tip electrode is a needle-shaped structure made of conductive material (length 29 mm, diameter 1 mm, one end is sharp), and the non-needle tip end of each needle tip electrode is independently welded to a pad (the needle tip electrode and the pad are connected one-to-one), and is electrically connected to the pad; the number of needle tip electrodes is the same as the number of fiber colonies in the array gradient nanofiber membrane;

[0026] The connector is located at the edge of the printed circuit board and distributed on the diagonal of the printed circuit board, and the pad is electrically connected to the connector through a wire, and the connector is used for grounding.

[0027] The insulating substrate can be located on a general roller receiver (the roller receiver refers to the record in CN113130807A), and the side of the insulating substrate facing away from the annular electrode is tangent to the surface of the roller in the roller receiver, and the tip of the needle electrode faces the spinning needle of the electrospinning. An insulating layer (such as a non-woven fabric and / or foam, for the purpose of insulation) is also arranged between the printed circuit board and the roller receiver. This placement is to facilitate the preparation of nanomaterials, because the electrospinning equipment itself includes a roller receiver, and the printed circuit board is located above the roller receiver to better fix it (the two can be fixed with double-sided tape).

[0028] The polymer is one or more of PCL, PLGA, collagen and gelatin; the solvent is hexafluoroisopropanol; and the concentration of the spinning solution is 0.1-0.2 g / mL.

[0029] The electrospinning process is as follows: injection speed of 0.1-1 mL / h, spinning voltage of 10-20 kV, receiving distance of 10-20 cm, ambient temperature of 25±1° C., ambient relative humidity of 45±5%; vacuum drying at 40-60° C. for 3-6 hours.

[0030] A drug-loaded double-layer composite stent of the present invention is characterized in that the composite stent is prepared by the following method:

[0031] The double-layer composite scaffold was immersed in the cross-linking agent solution and placed in a 37°C constant temperature CO 2 The fiber membrane was incubated in an incubator for 20-40 min to activate the carboxyl groups on the fiber membrane, and then the excess crosslinker solution was removed to keep the fiber membrane moist. Then 100-110 μL SDF-1α was added to the fiber membrane and placed in a 37°C constant temperature CO incubator again. 2 Cultivate in an incubator for 3-5 hours to allow SDF-1α to be grafted onto the fiber membrane, wash, pre-freeze in liquid nitrogen for 10-20 minutes, and freeze-dry for 24-48 hours to obtain a drug-loaded double-layer composite stent (external hemostasis / internal repair double-layer composite stent);

[0032] The cross-linking agent is prepared by dissolving EDC and NHS (the mass ratio of EDC to NHS is 5:3) in MES buffer (pH 5.0-6.5), stirring for 2 hours until the solution is uniform, and obtaining a cross-linking agent solution.

[0033] The concentration of the cross-linking agent solution is 2.4-3.2 mg / ml; the concentration of the SDF-1α solution is 50-500 ng / mL.

[0034] The washing step is to rinse with PBS buffer 3-4 times, each time for 30 seconds.

[0035] The present invention provides an application of the drug-loaded double-layer composite stent in the preparation of a skin wound stent. The stent is composed of an outer layer chitosan sponge with a gradient pore structure having a hemostatic effect and an inner layer gradient nanofiber membrane having a tissue repair function, and can be applied to skin wounds with a certain depth. When a wound appears on the skin, the outer sponge of the drug-loaded double-layer composite stent will quickly absorb the blood at the wound and stop bleeding through the differential capillary effect formed by the gradient pore structure, and then the drug chemokine carried on the inner fiber membrane will show a gradient release, that is, the drug release concentration at the center of the fiber membrane is higher than that at the edge, which will recruit endogenous stem cells at the edge of the wound to the center of the wound to promote wound repair.

[0036] Beneficial Effects

[0037] (1) An external hemostasis / internal repair double-layer composite scaffold, which introduces the adhesive component dopamine to enhance the interlayer bonding force and adjust the pore size, so that the external hemostasis chitosan sponge layer and the internal repair fiber membrane layer are tightly combined while realizing the construction of the sponge layer gradient pore structure, forming a loose gradient porous sponge-radially oriented fiber composite structure, and obtaining an integrated wound hemostasis-repair material. In the loose gradient porous sponge-radially oriented fiber structure, the loose gradient porous layer has a hemostatic effect, has a high porosity and a high water absorption rate, and its pore size decreases from large to small in the direction away from the inner fiber membrane, presenting a gradient structure, which can produce a differential capillary effect, can quickly absorb blood from the wound, and can also capture red blood cells, so that the red blood cells adhere and aggregate to form a clot, and quickly stop bleeding; the radially oriented fiber layer has a cell guiding effect, and the radially oriented fiber structure can realize the release of chemokines at different concentrations from the center to the edge of the wound, which can guide the stem cells around the damaged area to migrate to the center of the wound, and promote the growth and adhesion of fibroblasts. The synergistic effect of the two accelerates wound repair.

[0038] (2) Compared with the prior art, the present invention enhances the interlayer bonding force by introducing the adhesion component dopamine, and at the same time controls the pore size of the chitosan sponge layer by controlling the amount of dopamine added, so that it presents a gradient pore structure that can quickly absorb liquid, thereby preparing an external hemostasis / internal repair double-layer composite stent, avoiding the introduction of an adhesive layer, having the characteristics of being non-toxic, and having good biocompatibility.

[0039] (3) The chitosan sponge prepared by the present invention has good shape recoverability. When the chitosan sponge is compressed and deformed, it can quickly absorb liquid and swell and return to its original shape when placed in water or blood.

[0040] (4) The external hemostasis / internal repair double-layer composite stent was used in a rat full-thickness skin injury model. Twelve days after surgery, the wound closure rate could reach 97%, and the repair effect was significant. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 Schematic diagram of the external hemostasis / internal repair double-layer composite stent; wherein 1-internal repair electrospun fiber membrane 2-external hemostasis chitosan sponge macroporous area 3-external hemostasis chitosan sponge microporous area;

[0042] Figure 2 This is a physical picture of the external hemostasis / internal repair double-layer composite stent;

[0043] Figure 3 It is a schematic diagram of the receiving device structure (front view); wherein 1-printed circuit board 2-connector 3-ring electrode 4-needle tip electrode;

[0044] Figure 4 Schematic diagram of the receiving device structure (top view); 1-printed circuit board 2-connector 3-ring electrode 4-needle tip electrode;

[0045] Figure 5 It is a schematic diagram of the receiving device structure (bottom view); 5-wire 6-pad. DETAILED DESCRIPTION

[0046] The present invention is further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application. Raw materials used in the examples and comparative examples are:

[0047] PCL (average molecular weight 80,000; purchased from Aldrich Chemistry), PLGA (polylactic acid: polyglycolic acid = 75:25, intrinsic viscosity 0.8 dl / g; purchased from Jinan Daigang Bioengineering Co., Ltd.), gelatin (gel strength ~260g Bloom; purchased from Shanghai McLean Biochemical Technology Co., Ltd.); collagen (derived from rat tail, purchased from Chengdu McCahey Chemical Co., Ltd.)

[0048] The peeling performance test of the sponge / fiber membrane double-layer composite scaffold prepared in the embodiment was carried out using an electronic universal material testing machine. The specific steps are: tear half of the area between the inner gradient fiber membrane and the outer sponge with tweezers, and then use glue to hold the inner fiber membrane and the outer sponge with transparent polyethylene plates respectively, and then use the universal material testing machine to perform a peeling test on them, and the test parameters are: clamping distance 5cm, peeling speed 50mm / min.

[0049] Example 1

[0050] A receiving device for electrospinning (such as Figure 5 As shown), comprising a printed circuit board and a ring electrode made of stainless steel;

[0051] The printed circuit board includes an insulating substrate, 9 pads, two connectors, 9 wires and 9 needle-tip electrodes; the 9 pads are distributed on the insulating substrate in the following manner: the pad is regarded as a point, one pad is distributed in the exact center of the insulating substrate, and the remaining 8 pads constitute a circular array pad group, and the pads on the circular array pad group are distributed at equal angles along the circumference; the center of the ring is the exact center of the insulating substrate.

[0052] The bottom of the annular electrode is fixed on the insulating substrate, and from the top perspective of the annular electrode, the circle formed by the inner wall of the annular electrode and the circle formed by the annular array pad group form concentric circles, and the radius of the circle formed by the annular array pad group is half of the circle formed by the inner wall of the annular electrode; the radius of the circle formed by the inner wall of the annular electrode is 6.5 mm; and the thickness of the annular electrode (made of stainless steel) is 1 mm and the height is 27 mm;

[0053] The needle tip electrode is a needle-shaped structure made of conductive material (length 29 mm, diameter 1 mm, one end is sharp), and the non-needle tip end of each needle tip electrode is independently welded to a pad (the needle tip electrode and the pad are connected one-to-one), and is electrically connected to the pad; the number of needle tip electrodes is the same as the number of fiber colonies in the array gradient nanofiber membrane;

[0054] The connector is located at the edge of the printed circuit board and distributed on the diagonal of the printed circuit board, and the pad is electrically connected to the connector through a wire, and the connector is used for grounding.

[0055] The insulating substrate is located on a roller receiver (the roller receiver is described in CN113130807A), and the side of the insulating substrate facing away from the annular electrode is tangent to the surface of the roller in the roller receiver, and the tip of the needle electrode faces the spinning needle of the electrospinning. A non-woven fabric is also arranged between the printed circuit board and the roller receiver as an insulating layer.

[0056] Example 2

[0057] The preparation method of the external hemostasis / internal repair double-layer composite stent comprises the following steps:

[0058] (1) Preparation of spinning solution: PLGA and gelatin were dissolved in hexafluoroisopropanol and stirred for 24 h until completely dissolved to obtain a spinning solution with a concentration of 0.1 g / mL; wherein the mass ratio of PLGA to gelatin was 8:2.

[0059] (2) Electrospinning is performed with the spinning solution prepared in step 1 to obtain a radially oriented array nanofiber membrane. The receiving device used in the electrospinning is the device designed in Example 1; the process parameters of the electrospinning are: injection speed of 1 mL / h, spinning voltage of 20 kV, receiving distance of 10 cm, ambient temperature of 25±1°C, and ambient relative humidity of 45±5%. The prepared fiber membrane is then vacuum dried at 40°C for more than 3 hours and stored for later use.

[0060] (3) Dissolve two portions of chitosan powder in 1% acetic acid solvent respectively, stir for 12 h to obtain a mixed solution with a concentration of 20 mg / mL; then add dopamine to the mixed solution, stir in a 40°C water bath for 1 h, wherein the mass ratios of the added chitosan powder and dopamine are 4:1 and 1:1, respectively; continue to add genipin to the mixed solution, stir at room temperature for 10 min, and obtain mixed solution 1 and mixed solution 2; wherein the mass ratio of the added chitosan powder to genipin is 25:1.

[0061] (4) The fiber membrane obtained in step 2 is placed at the bottom of a circular hole plate with a diameter of 1.5 cm, and then 0.4 mL of the mixed solution 1 prepared in step 3 is poured onto the surface of the fiber membrane, and then 0.4 mL of the mixed solution 2 is poured onto the mixed solution 1, and then it is placed in a 4°C refrigerator for 12 hours to fully cross-link the chitosan through genipin, and then it is placed in liquid nitrogen for pre-freezing for 20 minutes, and then it is taken out and placed in a freeze dryer for freeze-drying for 12 hours, and then it is placed in 70% ethanol and soaked for 6 hours to chemically combine the chitosan sponge and the fiber membrane through dopamine to increase the interlayer interaction force, and then it is taken out and soaked in PBS solution for 3-4 times to wash off the excess ethanol, each time for 5 minutes, and then it is taken out and placed in liquid nitrogen for pre-freezing for 20 minutes, and then it is placed in a freeze dryer for freeze-drying for 3 hours to obtain a chitosan sponge / fiber membrane double-layer composite scaffold.

[0062] (5) EDC and NHS powders in a mass ratio of 5:3 were dissolved in MES buffer with a pH of 5.0-6.5 and stirred for 2 h to obtain a cross-linker solution with a concentration of 2.4 mg / mL.

[0063] (6) The chitosan sponge / fiber membrane double-layer composite scaffold obtained in step 4 is completely immersed in the crosslinker solution obtained in step 5 and placed in a 37°C constant temperature CO 2 The fiber membrane was incubated in an incubator for 20 min to activate the carboxyl groups on the fiber membrane, and then the excess crosslinker solution was removed to keep the fiber membrane wet. Subsequently, 100 μL of 500 ng / mL SDF-1α solution was added to the fiber membrane and placed in a 37°C constant temperature CO incubator again. 2 The samples were cultured in an incubator for 3 h to allow SDF-1α to be grafted onto the fiber membrane. The grafted samples were taken out and rinsed with PBS buffer for 3-4 times, each time for 30 s, to obtain an external hemostasis / internal repair double-layer composite scaffold.

[0064] Example 3

[0065] The preparation method of the external hemostasis / internal repair double-layer composite stent comprises the following steps:

[0066] (1) Preparation of spinning solution: PLGA and collagen were dissolved in hexafluoroisopropanol and stirred for 48 h until completely dissolved to obtain a spinning solution with a concentration of 0.2 g / mL; wherein the mass ratio of PLGA to collagen was 8:2.

[0067] (2) Electrospinning is performed with the spinning solution prepared in step 1 to obtain a radially oriented array nanofiber membrane. The receiving device used in the electrospinning is the device designed in Example 1; the process parameters of the electrospinning are: injection speed of 0.5 mL / h, spinning voltage of 10 kV, receiving distance of 20 cm, ambient temperature of 25±1°C, and ambient relative humidity of 45±5%. The prepared fiber membrane is then vacuum dried at 45°C for more than 4 hours and stored for later use.

[0068] (3) Two portions of chitosan powder were dissolved in 1% acetic acid solvent respectively, and stirred for 12 h to obtain a mixed solution with a concentration of 15 mg / mL; dopamine was then added to the mixed solution, and stirred in a 40°C water bath, wherein the concentrations of dopamine were 5 mg / mL and 10 mg / mL respectively; genipin was continued to be added to the mixed solution, and after stirring at room temperature for 10 min, mixed solution 1 and mixed solution 2 were obtained; wherein the mass ratio of the added chitosan powder to genipin was 20:1.

[0069] (4) The fiber membrane obtained in step 2 is placed at the bottom of a circular hole plate with a diameter of 1.5 cm, and then 0.7 mL of the mixed solution 1 prepared in step 3 is poured onto the surface of the fiber membrane, and then 0.7 mL of the mixed solution 2 is poured onto the mixed solution 1, and then it is placed in a 4°C refrigerator for 13 hours to fully cross-link the chitosan through genipin, and then it is placed in liquid nitrogen for pre-freezing for 15 minutes, and then it is taken out and placed in a freeze dryer for freeze-drying for 16 hours, and then it is placed in 70% ethanol and soaked for 8 hours to chemically combine the chitosan sponge and the fiber membrane through dopamine to increase the interlayer interaction force, and then it is taken out and soaked in PBS solution for 3-4 times to wash off the excess ethanol, each time for 5 minutes, and then it is taken out and placed in liquid nitrogen for pre-freezing for 15 minutes again, and then it is placed in a freeze dryer for freeze-drying for 4 hours to obtain a chitosan sponge / fiber membrane double-layer composite scaffold.

[0070] (5) EDC and NHS powders in a mass ratio of 5:3 were dissolved in MES buffer with a pH of 5.0-6.5 and stirred for more than 2 h to obtain a cross-linker solution with a concentration of 2.8 mg / mL.

[0071] (6) The chitosan sponge / fiber membrane double-layer composite scaffold obtained in step 4 is completely immersed in the crosslinker solution obtained in step 5 and placed in a 37°C constant temperature CO 2 The fiber membrane was incubated in an incubator for 30 min to activate the carboxyl groups on the fiber membrane, and then the excess crosslinker solution was removed to keep the fiber membrane wet. Subsequently, 100 μL of 500 ng / mL SDF-1α solution was added to the fiber membrane and placed in a 37°C constant temperature CO incubator again. 2 The samples were cultured in an incubator for 3 h to allow SDF-1α to be grafted onto the fiber membrane. The grafted samples were taken out and rinsed with PBS buffer for 3-4 times, each time for 30 s, to obtain an external hemostasis / internal repair double-layer composite scaffold.

[0072] Example 4

[0073] The preparation method of the external hemostasis / internal repair double-layer composite stent comprises the following steps:

[0074] (1) Preparation of spinning solution: PCL and collagen were dissolved in hexafluoroisopropanol and stirred for 96 h until completely dissolved to obtain a spinning solution with a concentration of 0.18 g / mL, wherein the mass ratio of PCL to collagen was 7:3.

[0075] (2) Electrospinning was performed with the spinning solution prepared in step 1 to obtain a radially oriented array nanofiber membrane. The receiving device used in the electrospinning was the device designed in Example 1; the process parameters of the electrospinning were: injection speed of 0.1 mL / h, spinning voltage of 15 kV, receiving distance of 20 cm, ambient temperature of 25±1°C, and ambient relative humidity of 45±5%. The prepared fiber membrane was then vacuum dried at 50°C for more than 5 hours and stored for later use.

[0076] (3) Two portions of chitosan powder were dissolved in 1% acetic acid solvent respectively, and stirred for 12 h to obtain a mixed solution with a concentration of 10 mg / mL; dopamine was then added to the mixed solution, and stirred in a 40°C water bath for 1 h, wherein the concentrations of dopamine were 4 mg / mL and 8 mg / mL respectively; genipin was continued to be added to the mixed solution, and stirred at room temperature for 10 min to obtain mixed solution 1 and mixed solution 2, wherein the mass ratio of the added chitosan powder to genipin was 25:1.

[0077] (4) The fiber membrane obtained in step 2 is placed at the bottom of a circular hole plate with a diameter of 1.5 cm, and then 0.8 mL of the mixed solution 1 prepared in step 3 is poured onto the surface of the fiber membrane, and then 0.8 mL of the mixed solution 2 is poured onto the mixed solution 1, and then it is placed in a 4°C refrigerator for 15 hours to fully cross-link the chitosan through genipin, and then it is placed in liquid nitrogen for pre-freezing for 10 minutes, and then it is taken out and placed in a freeze dryer for freeze-drying for 20 hours, and then it is placed in 80% ethanol and soaked for 8 hours to chemically combine the chitosan sponge and the fiber membrane through dopamine to increase the interlayer interaction force, and then it is taken out and soaked in PBS solution for 3-4 times to wash off the excess ethanol, each time for 5 minutes, and then it is taken out and placed in liquid nitrogen for pre-freezing for 10 minutes again, and then it is placed in a freeze dryer for freeze-drying for 5 hours to obtain a chitosan sponge / fiber membrane double-layer composite scaffold.

[0078] (5) EDC and NHS powders in a mass ratio of 5:3 were dissolved in MES buffer with a pH of 5.0-6.5 and stirred for more than 2 h to obtain a cross-linker solution with a concentration of 2.8 mg / ml.

[0079] (6) The chitosan sponge / fiber membrane double-layer composite scaffold obtained in step 4 is completely immersed in the crosslinker solution obtained in step 5 and placed in a 37°C constant temperature CO 2 The fiber membrane was incubated in an incubator for 40 min to activate the carboxyl groups on the fiber membrane, and then the excess cross-linking agent solution was removed to keep the fiber membrane wet. Subsequently, 100 μL of 100 ng / mL SDF-1α solution was added to the fiber membrane and placed in a 37°C constant temperature CO incubator again. 2 The samples were cultured in an incubator for 4 h to allow SDF-1α to be grafted onto the fiber membrane. The grafted samples were taken out and rinsed with PBS buffer for 3-4 times, each time for 30 s, to obtain an external hemostasis / internal repair double-layer composite scaffold.

[0080] Example 5

[0081] The preparation method of the external hemostasis / internal repair double-layer composite stent comprises the following steps:

[0082] (1) Preparation of spinning solution: PCL and gelatin were dissolved in hexafluoroisopropanol and stirred for 72 h until completely dissolved to obtain a spinning solution with a concentration of 0.15 g / mL, wherein the mass ratio of PCL to gelatin was 7:3.

[0083] (2) Electrospinning was performed with the spinning solution prepared in step 1 to obtain a radially oriented array nanofiber membrane. The receiving device used in the electrospinning was the device designed in Example 1; the process parameters of the electrospinning were: injection speed of 0.2 mL / h, spinning voltage of 13 kV, receiving distance of 15 cm, ambient temperature of 25±1°C, and ambient relative humidity of 45±5%. The prepared fiber membrane was then vacuum dried at 60°C for more than 6 hours and stored for later use.

[0084] (3) Two portions of chitosan powder were dissolved in 1% acetic acid solvent respectively, and stirred for 12 h to obtain a mixed solution with a concentration of 15 mg / mL; dopamine was then added to the mixed solution, and stirred in a 40°C water bath for 1 h, wherein the concentrations of dopamine were 3 mg / mL and 9 mg / mL respectively; genipin was continued to be added to the mixed solution, and after stirring at room temperature for 10 min, mixed solution 1 and mixed solution 2 were obtained, wherein the mass ratio of the added chitosan powder to genipin was 25:1.

[0085] (4) The fiber membrane obtained in step 2 is placed at the bottom of a circular hole plate with a diameter of 1.5 cm, and then 0.6 mL of the mixed solution 1 prepared in step 3 is poured onto the surface of the fiber membrane, and then 0.6 mL of the mixed solution 2 is poured onto the mixed solution 1, and then it is placed in a 4°C refrigerator for more than 16 hours to fully cross-link the chitosan through genipin, and then it is placed in liquid nitrogen for pre-freezing for 15 minutes, and then it is placed in a freeze dryer for freeze-drying for 24 hours, and then it is placed in 90% ethanol and soaked for 10 hours to chemically combine the chitosan sponge and the fiber membrane through dopamine to increase the interlayer interaction force, and then it is taken out and soaked in PBS solution for 3-4 times to wash off the excess ethanol, each time for 5 minutes, and then it is taken out and placed in liquid nitrogen for pre-freezing for 15 minutes again, and then it is placed in a freeze dryer for freeze-drying for 6 hours to obtain a chitosan sponge / fiber membrane double-layer composite scaffold.

[0086] (5) EDC and NHS powders in a mass ratio of 5:3 were dissolved in MES buffer with a pH of 5.0-6.5 and stirred for more than 2 h to obtain a cross-linker solution with a concentration of 3.2 mg / ml.

[0087] (6) The chitosan sponge / fiber membrane double-layer composite scaffold obtained in step 4 is completely immersed in the crosslinker solution obtained in step 5 and placed in a 37°C constant temperature CO 2 The fiber membrane was incubated in an incubator for 30 min to activate the carboxyl groups on the fiber membrane, and then the excess cross-linking agent solution was removed to keep the fiber membrane wet. Subsequently, 100 μL of 500 ng / mL SDF-1α solution was added to the fiber membrane and placed in a 37°C constant temperature CO incubator again. 2 After culturing in an incubator for 5 hours, SDF-1α was grafted onto the fiber membrane to obtain an external hemostasis / internal repair double-layer composite scaffold.

[0088] Comparative Example 1

[0089] The preparation method of the radiation-oriented array nanofiber membrane for repair is as follows:

[0090] (1) Preparation of spinning solution: PCL and gelatin were dissolved in hexafluoroisopropanol and stirred for 72 h until completely dissolved to obtain a spinning solution with a concentration of 0.15 g / mL, wherein the mass ratio of PCL to gelatin was 7:3.

[0091] (2) Electrospinning was performed with the spinning solution prepared in step 1 to obtain a radially oriented array nanofiber membrane. The receiving device used in the electrospinning was the device designed in Example 1; the process parameters of the electrospinning were: injection speed of 0.2 mL / h, spinning voltage of 13 kV, receiving distance of 15 cm, ambient temperature of 25±1°C, and ambient relative humidity of 45±5%. The prepared fiber membrane was then vacuum dried at 60°C for more than 6 hours and stored for later use.

[0092] (3) EDC and NHS powders in a mass ratio of 5:3 were dissolved in MES buffer with a pH of 5.0-6.5 and stirred for more than 2 h to obtain a cross-linker solution with a concentration of 3.2 mg / mL.

[0093] (4) The nanofiber membrane obtained in step 2 is completely immersed in the crosslinker solution obtained in step 3 and placed in a 37°C constant temperature CO 2 The fiber membrane was incubated in an incubator for 30 min to activate the carboxyl groups on the fiber membrane, and then the excess crosslinker solution was removed to keep the fiber membrane wet. Subsequently, 100 μL of 500 ng / mL SDF-1α solution was added to the fiber membrane and placed in a 37°C constant temperature CO incubator again. 2 The samples were cultured in an incubator for 5 h to allow SDF-1α to be grafted onto the fiber membrane. The grafted samples were taken out and rinsed with PBS buffer for 3-4 times, each time for 30 s, to obtain an external hemostasis / internal repair double-layer composite scaffold.

[0094] Comparative Example 2

[0095] The preparation method of chitosan sponge with gradient pore structure for hemostasis comprises the following steps:

[0096] (1) Two portions of chitosan powder were dissolved in 1% acetic acid solvent respectively, and stirred for 12 h to obtain a mixed solution with a concentration of 15 mg / mL; dopamine was then added to the mixed solution, and stirred in a 40°C water bath for 1 h, wherein the concentrations of dopamine were 3 mg / mL and 9 mg / mL respectively; genipin was continued to be added to the mixed solution, and stirred at room temperature for 10 min to obtain mixed solution 1 and mixed solution 2, wherein the mass ratio of the added chitosan powder to genipin was 25:1.

[0097] (2) 0.6 mL of the mixed solution 1 prepared in step 1 was poured onto the bottom of a circular hole plate with a diameter of 1.5 cm, and then 0.6 mL of the mixed solution 2 was poured onto the mixed solution 1, and then placed in a 4°C refrigerator for more than 16 h to fully cross-link the chitosan with genipin, and then placed in liquid nitrogen for pre-freezing for 15 min, taken out and placed in a freeze dryer for freeze-drying for 24 h, and then placed in 90% ethanol for soaking for 10 h, and then taken out and placed in PBS solution for soaking 3-4 times to wash off excess ethanol, each time for 5 min, and then taken out and placed in liquid nitrogen for pre-freezing for 15 min again, and then placed in a freeze dryer for freeze-drying for 6 h to obtain a chitosan sponge with a gradient pore structure for hemostasis.

[0098] Comparative Example 3

[0099] The preparation method of the external hemostasis / internal repair double-layer composite scaffold is the same as that of Example 5, except that the receiving device used in the electrospinning in step (2) is only an ordinary roller receiver, and the inner repair layer fiber membrane obtained at this time is only a disordered stacked fiber membrane.

[0100] Comparative Example 4

[0101] The preparation method of the external hemostasis / internal repair double-layer composite scaffold is the same as that of Example 5, except that in step (1), only PCL is selected as the spinning solution. In this case, since PCL does not contain a carboxyl group, the inner repair layer fiber membrane obtained cannot be chemically bonded to the chitosan sponge and the fiber membrane using dopamine in step (4), and SDF-1α cannot be grafted onto the fiber membrane in step (6).

[0102] The macroscopic morphology of the chitosan sponge / fiber membrane double-layer composite scaffold prepared in Example 5 was characterized by a digital camera. Figure 2 As shown, 1 is a radially oriented array fiber membrane layer, and 2 is a chitosan sponge layer.

[0103] Comparative Example 5

[0104] (1) Preparation of spinning solution: PCL and gelatin were dissolved in hexafluoroisopropanol and stirred for 72 h until completely dissolved to obtain a spinning solution with a concentration of 0.15 g / mL, wherein the mass ratio of PCL to gelatin was 7:3.

[0105] (2) Electrospinning was performed with the spinning solution prepared in step 1 to obtain a radially oriented array nanofiber membrane. The receiving device used in the electrospinning was the device designed in Example 1; the process parameters of the electrospinning were: injection speed of 0.2 mL / h, spinning voltage of 13 kV, receiving distance of 15 cm, ambient temperature of 25±1°C, and ambient relative humidity of 45±5%. The prepared fiber membrane was then vacuum dried at 60°C for more than 6 hours and stored for later use.

[0106] (3) Two portions of chitosan powder were dissolved in 1% acetic acid solvent respectively, and stirred for 12 h to obtain a mixed solution with a concentration of 15 mg / mL; dopamine was then added to the mixed solution, and stirred in a 40°C water bath for 1 h, wherein the concentrations of dopamine were 3 mg / mL and 9 mg / mL respectively; genipin was continued to be added to the mixed solution, and after stirring at room temperature for 10 min, mixed solution 1 and mixed solution 2 were obtained, wherein the mass ratio of the added chitosan powder to genipin was 25:1.

[0107] (4) The fiber membrane obtained in step 2 is placed at the bottom of a circular hole plate with a diameter of 1.5 cm, and then 0.6 mL of the mixed solution 1 prepared in step 3 is poured onto the surface of the fiber membrane, and then 0.6 mL of the mixed solution 2 is poured onto the mixed solution 1, and then it is placed in a 4°C refrigerator for more than 16 hours to fully cross-link the chitosan through genipin, and then it is placed in liquid nitrogen for pre-freezing for 15 minutes, and then it is placed in a freeze dryer for freeze-drying for 24 hours, and then it is placed in 90% ethanol and soaked for 10 hours to chemically combine the chitosan sponge and the fiber membrane through dopamine to increase the interlayer interaction force, and then it is taken out and soaked in PBS solution for 3-4 times to wash off the excess ethanol, each time for 5 minutes, and then it is taken out and placed in liquid nitrogen for pre-freezing for 15 minutes again, and then it is placed in a freeze dryer for freeze-drying for 6 hours to obtain a chitosan sponge / fiber membrane double-layer composite scaffold.

[0108] In the animal experiment, each group of scaffolds was cut into a circular shape with a diameter of about 1 cm and sterilized by ultraviolet radiation. Then, a mouse full-thickness skin defect model was established (the wound was a circle with a diameter of 1 cm). The cut scaffolds were transplanted to the wound. The recovery of the wound on the back of the mouse was observed and photographed at the set time points. The wound area was measured using image J software. The wound healing rate can be calculated using the following formula:

[0109]

[0110] in:

[0111] S0 is the size of the skin defect area on the back of the mouse after surgery;

[0112] St is the wound area size on day t after surgery.

[0113] The performance indicators of the external hemostasis / internal repair double-layer composite stent are shown in Table 1.

[0114] Table 1 Performance data of the embodiment

[0115]

Claims

1. A double-layer composite stent, characterized in that: The double-layer composite scaffold comprises an inner layer of radially oriented array nanofiber membrane and an outer layer of sponge with gradient pore structure; The double-layer composite stent comprises: an inner layer of radially oriented nanofiber membrane (1), an outer hemostatic chitosan sponge macroporous region (2), and an outer hemostatic chitosan sponge microporous region (3); wherein the pore size of the outer hemostatic chitosan sponge macroporous region is in the range of 120-200 μm; and the pore size of the outer hemostatic chitosan sponge microporous region is in the range of 30-80 μm; The radially oriented array nanofiber membrane is specifically: The radially oriented array nanofiber membrane is composed of 9 fiber colonies, and the average thickness at the center of the 9 fiber colonies is 30 to 65 μm; in each fiber colony, the length direction of the fiber is radially distributed around the center of the fiber colony, and the density of the fiber is gradually reduced along the radial direction; The distribution of the nine fiber colonies is as follows: the center of the fiber colony is regarded as the fiber colony, one of the fiber colonies is taken as the center, and the other eight fiber colonies form a ring array fiber colony group, the ring array fiber colony group is distributed in a circle, and each fiber colony on the ring array fiber colony group is distributed at equal angles along the circumference; The fiber density at the connection point between any two fiber colony centers is higher than that at other locations between the two fiber colonies, and the connection point refers to a line connecting the centers of the two fiber colonies.

2. A method for preparing the double-layer composite stent according to claim 1, comprising: (1) dissolving chitosan in a solvent and stirring uniformly to obtain a chitosan solution, dividing the solution into two portions and adding different amounts of dopamine to each portion, stirring in a water bath, and then adding genipin and stirring to obtain a mixed solution A and a mixed solution B; (2) placing the radially oriented array nanofiber membrane at the bottom of the template, and then firstly pouring the mixed solution A of step (1) onto the surface of the fiber membrane, and then pouring the mixed solution B onto the mixed solution A, placing it at 4°C for 12-16 hours, and then pre-freezing it in liquid nitrogen for 10-20 minutes, taking it out and freeze-drying it for 12-24 hours, then soaking it in ethanol, soaking it in PBS solution, and then taking it out and pre-freezing it in liquid nitrogen for 10-20 minutes, and then freeze-drying it for 3-6 hours to obtain a double-layer composite scaffold; The preparation method of the radially oriented array nanofiber membrane is as follows: The polymer is dissolved in a solvent and stirred for 24-96 hours until it is completely dissolved to obtain a spinning solution, and then the spinning solution is placed in a micro-syringe, and electrospinned and vacuum dried to obtain a radially oriented array nanofiber membrane; wherein the receiving device used in electrospinning includes a printed circuit board and a ring electrode; The printed circuit board includes an insulating substrate, 9 pads, two connectors, 9 wires and 9 needle-tip electrodes; the 9 pads are distributed on the insulating substrate in the following manner: the pad is regarded as a point, one pad is distributed in the exact center of the insulating substrate, and the remaining 8 pads constitute a ring array pad group, and the pads on the ring array pad group are distributed at equal angles along the circumference; the center of the ring is the exact center of the insulating substrate; The bottom of the annular electrode is fixed on the insulating substrate, and from the top perspective of the annular electrode, the circle formed by the inner wall of the annular electrode and the circle formed by the annular array pad group form concentric circles, and the radius of the circle formed by the annular array pad group is half of the circle formed by the inner wall of the annular electrode; the radius of the circle formed by the inner wall of the annular electrode is 5-10mm; and the annular electrode is made of stainless steel, with a thickness of 1mm and a height of 27mm; The needle tip electrode is a needle-shaped structure made of conductive material, with a length of 29 mm, a diameter of 1 mm, and a sharp end. The non-needle tip end of each needle tip electrode is independently welded to a pad. The needle tip electrode and the pad are connected one-to-one and electrically connected to the pad. The number of needle tip electrodes is the same as the number of fiber colonies in the array nanofiber membrane. The connector is located at the edge of the printed circuit board and is distributed on the diagonal of the printed circuit board, and the pad is electrically connected to the connector through a wire, and the connector is used for grounding; The insulating substrate is located on the roller receiver, and the side of the insulating substrate facing away from the annular electrode is tangent to the surface of the roller in the roller receiver, and the tip of the needle electrode faces the spinning needle of the electrospinning; an insulating layer is also arranged between the printed circuit board and the roller receiver.

3. The preparation method according to claim 2, characterized in that: In the step (1), the concentration of dopamine in the mixed solution A is 2-5 mg / mL; the concentration of dopamine in the mixed solution B is 7-10 mg / mL.

4. The preparation method according to claim 2, characterized in that: In the step (1), the concentration of chitosan after being dissolved in the solvent is 10-20 mg / mL; the solvent is acetic acid with a volume percentage concentration of 1%; the mass ratio of chitosan to dopamine is (1-4):1; the mass ratio of chitosan to genipin is (20-25):

1.

5. The preparation method according to claim 2, characterized in that: The radially oriented array nanofiber membrane in step (2) is a polymer radially oriented array nanofiber membrane, wherein the polymer is one or more of polycaprolactone PCL, polylactic acid-glycolic acid copolymer PLGA, collagen, and gelatin.

6. The preparation method according to claim 2, characterized in that: In the step (2), the template is a circular hole plate with a diameter of 1.5 cm; the perfusion volume of the mixed solution A and the mixed solution B is 0.5-0.8 mL respectively.

7. The preparation method according to claim 2, characterized in that: In the step (2), the ethanol soaking is performed in 70-90% ethanol by mass concentration for 6-10 hours; and the PBS solution is soaked 3-4 times, each time for 3-5 minutes.

8. A drug-loaded double-layer composite stent, characterized in that: The drug-loaded double-layer composite stent is prepared by the following method: The double-layer composite scaffold of claim 1 is immersed in a crosslinking agent solution and placed in a 37°C constant temperature CO2 incubator for 20-40 minutes to activate the carboxyl groups on the fiber membrane, and then the excess crosslinking agent solution is removed to keep the fiber membrane in a wet state. Then, 100-110 μL of SDF-1α was added dropwise to the fiber membrane, and the membrane was placed in a 37°C constant temperature CO2 incubator for 3-5 hours to allow SDF-1α to be grafted onto the fiber membrane. The membrane was then washed, pre-frozen in liquid nitrogen for 10-20 minutes, and freeze-dried for 24-48 hours to obtain a drug-loaded double-layer composite scaffold. The concentration of SDF-1α solution is 50-500 ng / mL; The cross-linking agent is prepared by dissolving EDC and NHS in MES buffer and stirring until the solution is uniform to obtain a cross-linking agent solution; the concentration of the cross-linking agent solution is 2.4-3.2 mg / ml; the mass ratio of EDC to NHS is 5:3; and the pH of the MES buffer is 5.0-6.

5.

9. The composite stent according to claim 8, characterized in that: The concentration of the SDF-1α solution is 100-500 ng / mL.

10. Use of the drug-loaded double-layer composite stent according to claim 8 in preparing a skin wound stent.

Citation Information

Patent Citations

  • Light-emitting device and preparation method and application thereof

    CN113130807A

  • Multilayer centripetal oriented nano fiber artificial dura mater and preparation method thereof

    CN107875448A

  • Manufacturing method of wound protection hemostatic material and products made by the same

    TW201100128A